Revolutionizing Cardiovascular Treatments with the Use of AI: Current Status and Future Prospects - Szymańska, Katarzyna; Szmyt, Katarzyna; Krasnoborska, Julia; Samojedny, Sylwia; Superson, Maciej; Walczak, Kamil; Wilk-Trytko, Klaudia; Zarębska, Julia; Duplaga, Tomasz Andrzej (Quality in Sport, 2024)
Introduction: Artificial Intelligence (AI) has emerged as a seminal force in healthcare, fundamentally transforming various aspects of medical practice and patient care. This review explores the transformative impact of AI on the treatment of cardiovascular diseases (CVDs). State of Knowledge: AI has revolutionized diagnostic accuracy, treatment precision, and patient management in the realm of cardiovascular care. It enhances diagnostic processes, enabling the early detection of CVDs through advanced imaging analysis and interpretation. Additionally, AI facilitates precision in risk stratification, identifying high-risk patient cohorts with heightened accuracy and informing personalized treatment strategies. Furthermore, AI optimizes drug selection and dosage regimens through pharmacogenomics, maximizing therapeutic efficacy while minimizing adverse drug reactions. Moreover, AI improves precision and safety during interventional procedures, guiding clinicians in real-time decision-making and enhancing procedural outcomes. Conclusions: AI is poised to revolutionize cardiovascular care, fostering innovation and improving patient outcomes.